Associations between menu quality, foodservice quality, patient satisfaction, and trust among hospital inpatients: A PLS-SEM study - Sri Rahayu Yuni Mulyaningtyas; Nurul Muslihah; Irma Sarita Rahmawati (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Hospital nutrition services influence the quality of patient care; however, the mediating role of satisfaction in building patient trust remains underexplored. This cross-sectional study examined the associations between menu quality, foodservice quality, patient satisfaction, and patient trust among 385 Class III inpatients at Kanjuruhan Regional General Hospital, Indonesia (February–May 2025), recruited through consecutive sampling. Data were collected via structured interviews using a validated 32-item questionnaire (Cronbach's α=0.960). Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to examine the direct and indirect associations. Menu quality significantly influenced patient satisfaction (β=0.446, p<0.001) and trust (β=0.280, p<0.001). Foodservice quality significantly affected satisfaction (β=0.263, p<0.001) and trust (β=0.194, p=0.001) in the present study. Patient satisfaction strongly predicted trust (β=0.445, p<0.001) and partially mediated the effects of menu quality (indirect effect=0.198, p<0.001) and foodservice quality (indirect effect=0.117, p<0.001). The model explained 40.7% of the variance in satisfaction and 62.0% in trust. In conclusion, menu quality and foodservice quality were significantly associated with patient trust through both direct and satisfaction-mediated pathways. Enhancing these dimensions is a strategic priority for improving institutional trust in hospital nutrition services.